Effectiveness of α2agonists for sedation in paediatric critical care: study protocol for a retrospective cohort observational study. Issue 5 (30th May 2017) - Hayden, John C; Dawkins, Ian; Breatnach, Cormac; Leacy, Finbarr P; Foxton, June; Healy, Martina; Cousins, Gráinne; Gallagher, Paul J; Doherty, Dermot R
Abstract : Introduction: Mechanically ventilated children in paediatric intensive care units are commonly administered analgesics and sedative agents to minimise pain and distress and facilitate cooperation with medical interventions. Opioids and benzodiazepines are the most common analgesic and sedative agents but have safety concerns. The α2 agonists clonidine and dexmedetomidine are alternative sedatives in use despite neither having robust evidence to support their use. Studies evaluating effectiveness of α2 agonists to date have not focused on sedation-based outcomes instead focusing on opioid-sparing properties and ventilation outcomes. The aim of this study is to evaluate if an opioid-based sedation regimen, with an α2 agonist adjunct (clonidine or dexmedetomidine), produces a non-inferior proportion of time adequately sedated compared with a control group without an α2 agonist adjunct, while conferring potential additional benefits such as reduced opioid administration and less exposure to potential additional agents such as benzodiazepines. Methods and analysis: We will conduct a retrospective cohort study in two Irish paediatric intensive care units using clinical information on patient characteristics, sedation scores and drug use. Eligible children admitted between January 2014 and June 2016 who were mechanically ventilated and received an opioid infusion will be included. Patients will be categorised into two exposure categories (received an α2 agonist or did not receive an α2 agonist) and the time adequately sedated (measured using the COMFORT Behaviour Score) will be calculated using interpolation of nursing sedation scores at each recorded time point. At least 150 per group is planned for inclusion to ensure adequate study power. Propensity score matching will be used in analysis to account for potential confounding by indication. Ethics and dissemination: The study has been approved by the ethics committees of both hospitals. Dissemination will occur via local, national and international presentations for academic and healthcare audiences as well as through peer reviewed publications.